(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aims to find out: (1) The symbols contained in the Mappacci as a tradition of Bugis Bone Culture, (2) The meaning of the symbols contained in the Mappacci as a tradition of Bugis Bone Culture. The research method used is qualitative research with the main data used sourced from the interview with the informant, while secondary data through articles, documents, journals, reference books, sites on the internet related to research conducted. The results showed that there was a meaningful symbol in the mappacci wedding ceremony in the Bugis Bone culture. Symbolic meaning contained in Mappacci of Bugis Bone, as follows : 1) Pillow (Angkalungeng) is a symbol of prosperity and respect, 2) Silk (Lipa’ Sabbe) is a symbol of Self-esteem, consistency, and perseverance 3) Banana Leaf Shoot (Colli’ Daung) is a symbol of sustainable life, 4) Jackfruit Leaves (Daung Panasa) is a symbol of Honesty and aspiration, 5) Pacci (Daung Pacar) is a symbol of Purity or Cleanliness, 6) Candle is a symbol of Light, Live with peace and Harmony, 7) Metal Container Strong Bond, 8) Rice (Benno) is a symbol of Well developed, blooming and prospering, and 9) Brown Sugar and Coconut is a symbol of a sign of pleasure and togetherness.